Dinamika Komunikasi Nonverbal Dalam Interaksi Sosial Di Lingkungan Kerja: Studi Kasus Pada Perusahaan Startup - Almadina Rakhmaniar (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
This study aims to examine the patterns and impacts of nonverbal communication in social interactions in startup companies. The empirical findings of this study reveal some dominant nonverbal communication patterns as well as the significant impact of these patterns on team dynamics. The study also explores the influence of the unique characteristics of startup companies on the way nonverbal communication is conducted and received. The study found that in daily interactions in startup companies, several forms of nonverbal communication are used predominantly, Friendly and open facial expressions are used very frequently, Consistent but not too intense eye contact is the norm. This shows attention and trust between coworkers, but prolonged eye contact is avoided to keep the existing hierarchy in balance. Hand gestures are often used to clarify and emphasize key points during discussions and presentations. These gestures help convey messages more effectively and ensure better understanding among team members. Flexible and less formal use of space is a hallmark of startup companies. Many interactions take place in open spaces and shared work areas, which encourage collaboration and informal communication. Positive nonverbal communication patterns, such as consistent eye contact and supportive facial expressions, contribute to a high level of trust among team members. This trust strengthens collaboration and teamwork, which is essential in a startup environment that often requires close teamwork. found in brainstorming sessions and creative discussions, reflecting a dynamic and innovative work culture.